Voltage dependence of agonist effectiveness at the frog neuromuscular junction: resolution of a paradox. - Dionne, V E (1975)
1. End-plate currents produced by nerve-released acetylcholine and iontophoretically applied acetylcholine and carbachol have been recorded from voltage-clamped frog cutaneous pectoris neuromuscular junctions made visible with Nomarski differential interference contrast optics. 2. The effectiveness of agonists - that is, the end-plate conductance change produced by a given dose-has been determined as a function of post-junctional membrane potential. 3. As the post-junctional membrane potential is made more negative, nerve-released acetylcholine becomes less effective whereas iontophoretically-applied agonists become more effective. 4. This voltage dependence of agonist effectiveness is mediated neither by end-plate current iontophoresis of agonist into the cleft nor through electric field effects on the esterase. 5. Influences of membrane potential on the opening and closing of end-plate channel gates can account quantitatively for the voltage-dependent effectiveness of both nerve-released and iontophoretically applied agonist.